"Diastolic heart failure" or heart failure caused by subtle left ventricular systolic dysfunction?. Issue 1 (1st January 2002) - Petrie, M C; Caruana, L; Berry, C; McMurray, J J V
Abstract : Objectives: To determine whether patients with suspected heart failure but preserved systolic function, as determined by conventional echocardiographic measures (often said to have "diastolic heart failure), might have subtle left ventricular systolic dysfunction detectable by a new measure of left ventricular systolic function—left ventricular systolic atrioventricular plane displacement. Design: Observational study. Setting: Direct access echocardiography. Patients: 147 patients with suspected heart failure referred by general practitioners. Measurements: Echocardiographic assessment of conventional measures of left ventricular systolic function (fractional shortening, ejection fraction (by Simpson's biplane method) and "eyeball" assessment) and measurement of left ventricular systolic atrioventricular plane displacement. Results: Between 21% and 33% of patients with "normal" left ventricular systolic function by conventional methods were found to have abnormal left ventricular systolic atrioventricular plane displacement. Conclusions: Approximately one quarter of patients with suspected heart failure but preserved systolic function by conventional methods have abnormal atrioventricular plane displacement. These patients with suspected heart failure but preserved systolic function by conventional echocardiographic measures may have heart failure caused by subtle systolic dysfunction rather than isolated "diastolic heart failure".